TADLIS DALAM JUAL BELI : (Ditinjau Menurut Hukum Islam) - Syazali, Hasan (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2020)
Every person in maintaining his life a variety of activities carried out, one of which is very common activities they do is buying and selling. Sale and purchase contained in the community are very diverse in types, in the practice of buying and selling, each seller always puts forward the maximum profit, a variety of ways they do. One trait that is not praiseworthy about the seller is Tadlis. Tadlis is Hiding the defect of an item that one party (the seller) knows about, but does not inform the buyer. In trade the occurrence of exchange of interests as profit without doing unauthorized emphasis or acts of fraud against other groups. This is strictly prohibited in Islam because it contains an element of deception. Tadlis practice in buying and selling that occurs in the sale of goods does not explain in detail related to the condition of the goods, whether the goods are still good or not, besides that some buyers do not know the quality or quantity of goods, in the sale of fish/meat there is a mixing of fish/meat between qualities good and bad found in fish/meat piled up by traders as bad fish/meat is placed under fresh meat. Therefore, business practices carried out by someone by hiding information on buying and selling transactions (transactions that contain something that is not known by one party). Factors of occurrence of Tadlis in the sale of fish/meat in Pidie Market, Pidie Regency is profit factor, between sellers and buyers not doing khiyar during the sale and purchase transaction, there is no agreement between the seller and buyer, environmental factors, customs factors, economic factors, internal factors, and external factors.